Ethnographies of Uncertainty in Africa
XIII, 211 p.
Keywords: This collection explores the productive potential of uncertainty for people living in Africa as well as for scholars of Africa. Eight ethnographic case studies from across the continent examine how uncertainty is used to negotiate insecurity, create and conduct relationships, and act as a source for imagining the future.